The Other Story : Afro-Asian artists in post-war Britain - Araeen, Rasheed (London : South Bank Centre, 1989)
Araeen, Rasheed ; Arif, Saleem ; Bowling, Frank ; Boyce, Sonia ; Chambers, Eddie ; Chandra, Avinash ; Dhanjal, Avtarjeet ; Egonu, Ezo ; Geoffrey, Iqbal ; Hatoum, Mona ; Himid, Lubaina ; Jantjes, Gavin ; Khanna, Balraj ; Locke, Donald ; Medalla, David ; etc.
The Other Story : Afro-Asian artists in post-war Britain, Hayward Gallery, London, 29 November 1989 to 4 February 1990 ; Wolverhampton Art Gallery, Wolverhampton, 10 March to 22 April 1990 ; Manchester City Art Gallery and Cornerhouse, Manchester, 5 May to 10 June 1990
boek
Keywords: Afro-Aziatisch